THE STRENGTH OF THE SEEMINGLY UNRELATED REGRESSION MODEL IN DETECTING ECONOMIC GROWTH AND POVERTY RATE BASED ON FINANCIAL INCLUSION IN INDONESIA - Lia Nazliana Nasution; Ade Novalina; Rusiadi Rusiadi; Dewi Mahrani Rangkuty (SEAN Institute, 2023)
Financial inclusion has become an essential topic in recent years. Its impact on economic growth, poverty alleviation, and reducing income inequality is evident in several countries. Indonesia as a developing country, where economic growth has slowed in recent years, the level of use of formal financial services still needs to be increased, and the decline in the poverty rate, which is not followed by a low Gini ratio, is necessary to study further how financial inclusion affects economic growth and poverty rate in Indonesia. Using the Seemingly Unrelated Regression (SUR) model, we wanted to investigate the model's strength to achieve the objectives of this study. The results of the SUR model show that financial inclusion does not positively impact economic growth. However, we find the dimensions of availability of financial inclusion optimal for poverty alleviation and reducing income inequality well with significant adverse results. Meanwhile, the dimensions of accessibility and usability have no significant effect.